Vector Analysis of Anticipated Residual Astigmatism and Actual Residual Astigmatism in Toric IOL Implantation using Callisto-Eye - Kukuh Prasetyo; Ucok Pasaribu; Setiyobudi Riyanto; Johan Hutauruk (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2017)
Purpose: The aim of this study is to investigate the differences of actual residual astigmatism and anticipated residual astigmatism using Alpin’s Vector Analysis from toric IOL implantation using Image Guided System (Callisto EyeTM) and other method. Method: This was a retrospective case series study done in Jakarta Eyte Center. Data was taken consecutively from medical records of Toric IOL implantation from January 2016 to November 2017. Primary data taken were demographic data, anticipated residual astigmatism, refractive examination both subyectively and objectively. Secondary data was analized using Alpin’s Vector Analysis to substract anticipated residual astigmatism from actrual residual astigmatism. Spherical equivalent and axis shifting also taken from refractive ecamination results. Data was divided into subgrup of Toric IOL implantation using Image Guided System and subgrup of Toric IOL implantation using other method. Results: There was a statically significant difference of subjective refraction vector analysis result between subgroups with differnce of 0.312 dioptri (p value 0.004). Objective refraction vector analysis shows no statistically difference between two subgrups (p value 0.286). Spherical equivalent both subjectively and objectively not differ (p value 0.721 and 0,689). Axis shifting from refractive examination also not statistically significant differ between two subgrups (p value 0.432 and 0.358) Conclusion: Difference between actual residual astigmatism from subjective refraction and anticipated residual astigmatism is lower whrn usingCallisto EyeTM.